Antiweathering effects of vitamin E on wood flour/polypropylene composites. Issue 11 (20th January 2014) - Peng, Yao; Liu, Ru; Cao, Jinzhen; Luo, Shupin
<x xml:space="preserve">Abstract</x> The purpose of this research was to investigate the influence of vitamin E (Ve) with different loading levels (0.1, 0.2, 0.4, and 1.2 %wt) on the photodegradation of wood flour/polypropylene composites. Five groups of composites were exposed in a QUV‐accelerated weathering tester for 960 h and then the surface color and the flexural properties were tested. Besides, the surface morphology and chemical changes of the composites during weathering were analyzed by scanning electron microscopy, attenuated total reflectance fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy. The results revealed that (1) the addition of Ve had a positive effect on hindering the photooxidation process of the composites; (2) composites with higher Ve loading levels (0.4 and 1.2 %wt) showed better flexural properties, less color fading, cracks, and disclosure of wood fibers on surface after weathering; (3) Ve alleviated the chain scission of PP and the formation of carbonyl groups by reacting with free radicals that generated from photodegradation during weathering. Therefore, it could be an effective antiphotodegradation agent for the composites. POLYM. COMPOS., 35:2085–2093, 2014. © 2014 Society of Plastics Engineers